Kinetic Modeling of Flocculation and Coalescence in the System Emulsion of Water-Xylene-Terbutyl Oleyl Glycosides - Harsa Pawignya; Tutuk Djoko Kusworo; Bambang Pramudono (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
The development of a mathematical model for explaining the kinetics of flocculation and coalescence of emulsion droplets is essential to study the stability of an emulsion system of the kinetics of emulsion stability. Mathematic models was developed from the equation Van Den Tempel by modifying emulsion systems. The emulsion was made by mixing water-xylene and surfactant tert-butyl oleyl glycosides. This research studied the effect of stirrer speed on the value of flocculation rate constant (a) and coalescence rate constant (K). The model identified the emulsion development condition whether controlled by coalescence or flocculation. It was observed that under lower agitation speed (1000 rpm) the emulsion development was controlled by flocculation mechanism, while a faster agitation (2000 rpm or higher) exhibited coalescence controlled mechanism. The results confirmed that the 1st model was the most appropriate for water-xylene-TBOG emulsion system. From four models after fitting with experimental data, the most suitable model is 4th model, because it has the smallest error of 2.22 %.